Answer:
![x_1=-4.9373\\ \\x_2=10.9373](https://img.qammunity.org/2023/formulas/mathematics/college/3jja52c062vlwf7hk05xibmh573vtq3qm8.png)
Explanation:
I'm assuming you need the solution of this equation, let's solve it!
1. Write the expression.
![4(x-3)^2-252=0](https://img.qammunity.org/2023/formulas/mathematics/college/nqe9ys2grkv2cddk2iqdlnzlxhq7ysjkm9.png)
2. Solve the square parenthesis.
We are using the following property:
![(a-b)^2=a^2-2ab+b^2](https://img.qammunity.org/2023/formulas/mathematics/high-school/wij5s4hl5c81m5e13tfkbmm8jk6ed6srgr.png)
Let x be "a".
Let 3 be "b"
![(x-3)^2=\\ \\x^2-2x(3)+3^2=\\ \\x^2-6x+9](https://img.qammunity.org/2023/formulas/mathematics/college/4eycmf9k4ecepyyebqkaiv83bz72l0cmt4.png)
3. Take the result of the expansion and substitute it inside the parenthesis in the original expression.
![4(x^2-6x+9)-252=0](https://img.qammunity.org/2023/formulas/mathematics/college/lk21r281oj4sk6srssunladohozm8ur7rc.png)
4. Make the associative multiplifation with 4.
![(4)(x^2)+(4)(-6x)+(4)(9)-252=0\\ \\(4x^2)+(-24x)+(36)-252=0\\ \\4x^2-24x-216=0](https://img.qammunity.org/2023/formulas/mathematics/college/ltjjdnvl3wamrplpyj6qkta23lpo378ggb.png)
5.Simplify the expression.
![(4x^2)/(4) -(24x)/(4) -(216)/(4) =(0)/(4) \\ \\x^2-6x-54=0](https://img.qammunity.org/2023/formulas/mathematics/college/z46zpjm3lo7tqlk47hzk4j7wtwun3lgqpg.png)
6. Find the roots.
Let's do it by applying the formula for solving quadratic equation. This is the formula:
![x=(-b(+-)√(b^2-4ac) )/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/lavpzgggwfat6r2g7ra1ym6g07yf04d2de.png)
If you take a closer look, the equation has a ± symbol on the upper part to the right of -b, this means that either sum or substraction can be done to solve this equation. This means that we are going to get 2 solutions, always. Hence:
![x_1=(-b-√(b^2-4ac) )/(2a)\\ \\x_2=(-b+√(b^2-4ac) )/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/xyoim9tzrr2q05bs7qa5zhgjsi0dv2jqhj.png)
Tha values of a, b, and c are the following:
Since x² is being multiplied by 1, a= 1;
Since -6x is being multiplied by -6, b= -6;
Since -54 is a constant, c= .
Substitute in the 2 equations and find the roots (could be done with a calculator).
![x_1=(-(-6)-√((-6)^2-4(1)(-54)) )/(2(1))=-4.9373\\ \\x_2=x_1=(-(-6)+√((-6)^2-4(1)(-54)) )/(2(1))=10.9373](https://img.qammunity.org/2023/formulas/mathematics/college/h1djwz2t94jsxmyid47dohvgm870pas8h5.png)
7. Express your results.
.